Recurring Issues in Indonesia’s Islamic Education: The Needs for Religious Literacy - Muhammad Zuhdi; Sarwenda Sarwenda (Analisa: Journal of Social Science and Religion, 2020)
Religious education plays an important role in Indonesia, not only in religious schools but also in all schools and in community development. A number of studies show that Indonesian religious education currently faces challenges in managing the problem of religious radicalism, especially in the context of a conservative society. This research focuses on various religious problems in the community that teachers often encounter during their interactions in schools and communities, with specific reference to Islamic education. This research was conducted using the Focus Group Discussion method which involved 28 religious education teachers from DKI Jakarta, Banten, and West Java. This research explores recurring religious issues in Indonesian society that require further attention in developing religious education programs. Looking at it from the perspective of religious literacy, this study found that multiculturalism, tolerance, and prejudice are the most recurring problems in society. Recognizing the growing challenges to Indonesia's plural society, religious literacy can be used as an alternative destination for religious education. Religious education must be directed towards students’ correct understanding of various religious beliefs and traditions, in addition to strengthening the faith and practice of students' own religious beliefs.